White-spot Lesions and Gingivitis Microbiotas in Orthodontic Patients - Tanner, A.C.R. (SAGE Publications, 2012)
White-spot lesions (WSL) associated with orthodontic appliances are a cosmetic problem and increase risk for cavities. We characterized the microbiota of WSL, accounting for confounding due to gingivitis. Participants were 60 children with fixed appliances, aged between 10 and 19 yrs, half with WSL. Plaque samples were assayed by a 16S rRNA-based microarray (HOMIM) and by PCR. Mean gingival index was positively associated with WSL (p = 0.018). Taxa associated with WSL by microarray included Granulicatella elegans (p = 0.01), Veillonellaceae sp. HOT 155 (p < 0.01), and Bifidobacterium Cluster 1 (p = 0.11), and by qPCR, Streptococcus mutans (p = 0.008) and Scardovia wiggsiae (p = 0.04) Taxa associated with gingivitis by microarray included: Gemella sanguinis (p = 0.002), Actinomyces sp. HOT 448 (p = 0.003), Prevotella cluster IV (p = 0.021), and Streptococcus sp. HOT 071/070 (p = 0.023); and levels of S. mutans (p = 0.02) and Bifidobacteriaceae (p = 0.012) by qPCR. Species’ associations with WSL were minimally changed with adjustment for gingivitis level. Partial least-squares discriminant analysis yielded good discrimination between children with and those without WSL. Granulicatella, Veillonellaceae and Bifidobacteriaceae, in addition to S. mutans and S. wiggsiae, were associated with the presence of WSL in adolescents undergoing orthodontic treatment. Many taxa showed a stronger association with gingivitis than with WSL.